Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.7759/cureus.2555
|View full text |Cite
|
Sign up to set email alerts
|

A Pacemaker that was Avoided

Abstract: Thyroxine is an essential hormone in the human body and exerts many effects on the cardiovascular system. The low metabolic state in hypothyroidism causes bradycardia and reduced cardiac contractility leading to reduced cardiac output. Severe bradycardia and atrioventricular (AV) blocks secondary to hypothyroidism have also been reported. We present a case of severe hypothyroidism causing a high-grade AV block which was successfully treated with thyroxine hormone replacement without requiring cardiac pacemaker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 6 publications
0
5
0
Order By: Relevance
“… 2 Some scholars have reported an 87-year-old patient who developed high-grade atrioventricular block, which was successfully treated by supplementing thyroxine therapy and avoided the implantation of a pacemaker. 9 Schoenmakers et al reported an elderly patient with severe hypothyroidism and complete atrioventricular block, who was recovered after levothyroxine supplementation. 10 Our patient underwent intravenous temporary pacemaker because of severe bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“… 2 Some scholars have reported an 87-year-old patient who developed high-grade atrioventricular block, which was successfully treated by supplementing thyroxine therapy and avoided the implantation of a pacemaker. 9 Schoenmakers et al reported an elderly patient with severe hypothyroidism and complete atrioventricular block, who was recovered after levothyroxine supplementation. 10 Our patient underwent intravenous temporary pacemaker because of severe bradycardia.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a literature review and found that there are few reported cases of cardiogenic shock and malignant arrhythmia caused by hypothyroidism, resulting in difficulties in the early identification and diagnosis. Previous reports of AVB caused by hypothyroidism have mainly been reported in adults (1)(2)(3)(4)(5), but rarely in children (8). Zaki (9) et al reported a case of refractory cardiogenic shock in an infant with congenital hypothyroidism.…”
Section: Discussionmentioning
confidence: 99%
“…Harada et al reported a case of a myxedema coma in an elderly female pa-tient who presented with sick sinus syndrome and type two respiratory failure, which was successfully managed with thyroid hormone replacement (Harada et al, 2019). Also, Waseem et al (2018) reported a case of an elderly male with a history of undertreated hypothyroidism who presented with atrial fibrillation with a slow ventricular response as well as a high degree atrioventricular block. The atrioventricular block resolved upon increasing the dose of levothyroxine, thus avoiding the need for permanent pacemaker implantation (Lee et al, 1986).…”
Section: Discussionmentioning
confidence: 99%